Global modeling of the low‐ and middle‐latitude ionospheric D and lower E regions and implications for HF radio wave absorption. Issue 1 (20th January 2017) - Siskind, David E.; Zawdie, K. A.; Sassi, F.; Drob, D.; Friedrich, M.
Abstract: We compare D and lower E region ionospheric model calculations driven by the Whole Atmosphere Community Climate Model (WACCM) with a selection of electron density profiles made by sounding rockets over the past 50 years. The WACCM model, in turn, is nudged by winds and temperatures from the Navy Operational Global Atmospheric Prediction System‐Advanced Level Physics High Altitude (NOGAPS‐ALPHA). This nudging has been shown to greatly improve the representation of key neutral constituents, such as nitric oxide (NO), that are used as inputs to the ionospheric model. We show that with this improved representation, we greatly improve the comparison between calculated and observed electron densities relative to older studies. At midlatitudes, for both winter and equinoctal conditions, the model agrees well with the data. At tropical latitudes, our results confirm a previous suggestion that there is a model deficit in the calculated electron density in the lowermost D region. We then apply the calculated electron densities to examine the variation of HF absorption with altitude, latitude, and season and from 2008 to 2009. For low latitudes, our results agree with recent studies showing a primary peak absorption in the lower E region with a secondary peak below 75 km. For midlatitude to high latitude, the absorption contains a significant contribution from the middle D region where ionization of NO drives the ion chemistry. The difference in middle‐ to high‐latitude absorption from 2008 to 2009 is due to changes in the NO abundance near 80 km from changes in the wintertime mesospheric residual circulation. Plain Language Summary: The study of the lowermost ionosphere (60‐100 km) is one of the classic problems in aeronomy and dates back to the dawn of the radio age. The practical motivation for this interest is that this atmospheric region can absorb HF radiowaves. Despite this long history, fundamental questions about what controls HF radio absorption still remain. Here we present the first global model study that uses a general circulation model of the whole atmosphere to capture the variation of key trace constituents such as nitric oxide and atomic oxygen. We show that with this new constraint, a model of the lower ionosphere is now in good agreement with a selection of rocket electron density profiles made as long as a half century ago. Our comparison also confirms a recent suggestion of a fundamental problem in our understanding of what governs the free electron density at tropical latitudes below 70 km altitude. Finally, we show how using the general circulation model allows us to simulate the seasonal and year to year variation of HF radio absorption by simulating the upward propagation of weather disturbances from the troposphere and stratosphere. Key Points: Accurate representation of mesospheric neutral constituents important for D region simulations Theoretical calculations reveal a tropical electron density deficit below 75 km Absorption at 5 MHz peaks near 95 km in tropics; at higher latitudes there is a contribution near 80 km from nitric oxide ionization